The SUMMA Platform Prototype - Junczys-Dowmunt, Marcin; al, et (Software Demonstrations of the 15th Conference of the European Chapter of the Association for Computational Linguistics, 2017)
We present the first prototype of the SUMMA Platform: an integrated platform for multilingual media monitoring. The platform contains a rich suite of low-level and high-level natural language processing technologies: automatic speech recognition of broadcast media, machine translation, automated tagging and classification of named entities, semantic parsing to detect relationships between entities, and automatic construction / augmentation of factual knowledge bases. Implemented on the Docker platform, it can easily be deployed, customised, and scaled to large volumes of incoming media streams.